Teacher Professional Development Management from an Islamic Perspective - Miftah Kusuma Dewi; Supeno (Institut Agama Islam At-Tahdzib, 2025)
Teacher professionalism is a major factor in educational success, as teachers serve not only as transmitters of knowledge but also as moral and spiritual role models for students. In the context of Islamic education, teacher professional development must be based on Islamic values ​​that emphasize a balance between intellectual, moral, and spiritual competencies. This study uses a literature study method with a descriptive-analytical approach to analyze the concept and implementation of teacher professional development management from an Islamic perspective as well as Islamic managerial principles relevant to educational institutions. The results of the study indicate that teacher professional development management in Islam includes four main functions: planning (takhṭīṭ), organizing (tanẓīm), directing (tawjīh), and supervising (raqabah), which are oriented towards moral development, competency improvement, and the refinement of intentions and work ethics. Teacher professionalism is not only measured from pedagogical and professional aspects, but also from sincerity, trustworthiness, and noble character in carrying out duties. By implementing Islamic management based on the values ​​of monotheism, continuous development, and a work culture modeled after the Prophet Muhammad (peace be upon him), teachers can develop into competent individuals with noble character, and make their profession a form of devotion and worship to Allah Swt. These findings are expected to serve as a basis for Islamic educational institutions in designing comprehensive, sustainable, and spiritually oriented teacher development strategies.